“1985: Argentina, world power”. Desarrollismo and demographic projections in the press of the 150th anniversary (Quinto Sol, 2013)
With this work we expect to provide some clues to inaugurate the traffic towards a history of statistics in the civil society. Though the study of the official statistics has extended our knowledge of the past, its effects are not so evident in spaces that work at certain distance from the state. Hence the importance of examining the use of demographic projections in the press of “150th May´s Revolution anniversary”. With this intention, we have divided the text into three sections. In the first part, we will provide an inventory of the advances of Statistics´ history, mentioning its problems, theoretical approaches and pending matters. In the second paragraph, we will make a picture of the “Argentina desarrollista”, showing the conflicts that were shaping it. Finally, we will analyze the statistical production published by “Clarín” in 1960, examining its suppositions and the symbolic effects that it was trying to generate.
Keywords: desarrollismo; statistics' history; demographic projections; press; identity